2022
DOI: 10.1128/aem.02544-21
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Bacteria Dominate Catalase Expression during Microcystis Blooms

Abstract: Cyanobacterial harmful algal blooms (CHABs) threaten freshwater ecosystems globally through the production of toxins. Toxin production by cyanobacterial species and strains during CHABs varies widely over time and space, but the ecological drivers of the succession of toxin-producing species remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 114 publications
0
17
0
Order By: Relevance
“…There was greatest phylogenetic conservation in the presence of genes for decomposition of reactive oxygen species (ROS), nitrogen (N) and phosphorous (P) metabolism, and carbon concentrating mechanisms (CCM). None of the WLE Microcystis isolates contained katG , an enzyme used for the degradation of hydrogen peroxide (Bernroitner et al, 2009); katG was previously shown to be absent from most, but not all cells, in natural WLE Microcystis populations (Smith et al, 2022a). However, t2prx , a type 2 peroxiredoxin (Schuurmans et al, 2018), was present in every strain analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was greatest phylogenetic conservation in the presence of genes for decomposition of reactive oxygen species (ROS), nitrogen (N) and phosphorous (P) metabolism, and carbon concentrating mechanisms (CCM). None of the WLE Microcystis isolates contained katG , an enzyme used for the degradation of hydrogen peroxide (Bernroitner et al, 2009); katG was previously shown to be absent from most, but not all cells, in natural WLE Microcystis populations (Smith et al, 2022a). However, t2prx , a type 2 peroxiredoxin (Schuurmans et al, 2018), was present in every strain analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, the associated bacteria were more abundant than the Microcystis strains present within each culture (Fig 5, Table S1), though biases in DNA extraction could influence this result. Associated bacterial genomes were also queried for catalase genes, which degrade hydrogen peroxide, thus ameliorating ROS stress on Microcystis (Morris et al, 2008; Smith et al, 2022a). Of the 22 cultures, 17 cultures contained organisms with catalase genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations